Global Change Modulated Asian Inland Climate Since 7.3 Ma: Carbonate Manganese Records in the Western Qaidam Basin - Liu, Yudong; Yang, Yibo; Ye, Chengcheng; Yang, Rongsheng; Appel, Erwin; Fang, Xiaomin (Frontiers in Earth Science, 2021)
Late Cenozoic drying of the Asian inland has not only exerted a profound impact on the regional environment but also affected global climate as an important source of global atmospheric dust. Continuous and accurately dated sediment records from the Asian interior are pivotal to a better understanding of the evolutionary history of Asian inland drying and the associated driving mechanisms. In this study, we present a continuous record of climate change in the Asian interior spanning the past 7.3 Myr, reconstructed by the redox evolution of a paleolake in the western Qaidam Basin, NE Tibetan Plateau. The paleolake redox conditions are linked to the oxygen concentration of lake bottom water and lake level, and were revealed by the manganese (Mn) concentration in the carbonate fraction (leached by the diluted acetic acid) of the carbonate-rich lacustrine sediments retrieved from two drill-cores (SG-1 and SG-1b). The reconstructed regional climate in the western Qaidam Basin shows long-term fluctuations, consistent with the secular evolution of the coeval global climate, especially the sea surface temperature variation in the high latitude North Atlantic. Three transitions of the paleolake hydrochemical system occurred at 6.2 Ma, 5.3 Ma, and 2.6 Ma, with a short drying stage at 6.2-5.3 Ma and prolonged Quaternary drying since 2.6 Ma. We argue that drying of the Asia interior has been dominantly forced by global cooling, in particular, the high-latitude cooling of the Northern Hemisphere.